PENGARUH DIGITAL CULTURE, LEADERSHIP STYLE, DAN ORGANIZATIONAL COMMITMENT TERHADAP WORKFORCE AGILITY PADA PT. BUMI ASRI LESTARI SITUBONDO - Azizah, Afrilia Nurul; Setyowati, Trias; Winahyu, Pawestri (Bisnis-Net, 2025)
Rapid digital transformation requires organisations to have a workforce that is adaptive and responsive to change. PT Bumi Asri Lestari Situbondo, as a company in the field of aquaculture, faces challenges in managing human resources in the midst of ever-changing technological developments. This study aims to examine the influence of digital culture, leadership style and organisational commitment on workforce agility. This research uses a descriptive quantitative approach with data collection through a Likert scale questionnaire. The sampling technique was proportionate random sampling, and data analysis was conducted using multiple linear regression. The results showed that the three independent variables namely digital culture, leadership style, and organisational commitment had a positive and significant effect on workforce agility. Digital culture plays a role in encouraging collaboration and the use of work technology, effective leadership style creates a supportive and communicative work environment, while organisational commitment increases employee loyalty and engagement in change. The findings suggest the importance of integration between digital culture, adaptive leadership and organisational commitment in shaping an agile workforce ready to face the dynamics of the digital era.